Impact of Corporate Social Responsibility on Brand Extension Success Via Organizational Trust: Moderating Role of the CSR Communication - Qasim, Saba; Siam, Mohammad R.A; Sallaeh, Salniza Bt Md; Rabie, Osaid (Asian Journal of Empirical Research, 2017)
This study investigated the moderated mediation mechanism through which corporate social responsibility affects brand extension success. This study posits that organizational trust mediates the relationship between corporate social responsibility and brand extension success. We further hypothesized that the CSR communication would moderate this process; high CSR communication would strengthen the effect of CSR on brand extension success. The findings showed that CSR positively affects brand extension success via organizational trust. Data were obtained from 316 consumers who have knowledge of the CSR actions of various organizations operating in Pakistan and brand extension. We have selected those organizations for our data collection which are doing CSR in Pakistan. Results are discussed in terms of their implications for both research and practice.